Controversies in the management of parathyroid carcinoma: A case series and review of the literature. (April 2016) - Medas, Fabio; Erdas, Enrico; Loi, Giulia; Podda, Francesco; Pisano, Giuseppe; Nicolosi, Angelo; Calò, Pietro Giorgio
Abstract: Parathyroid carcinoma is a rare malignancy representing less than 1% of primary hyperparathyroidism cases. Its management is controversial due to lack of large-scale, multicentric studies. We report 8 new cases of parathyroid carcinoma and review the literature. Preoperative diagnosis of carcinoma was possible in 2 (25%) cases. Unclear surgical margins were present in 5 (62.5%) patients; 4 of them underwent subsequent re-exploration and ipsilateral hemithyroidectomy, in one case associated to central lymph node dissection. Recurrent disease is reported in 2 (25%) patients. Considering the high incidence of local recurrence in case of unclear surgical margins, a re-exploration with ipsilateral hemithyroidectomy is indicated in these patients. A neck dissection should be performed only in case of clinically involved lymph nodes, avoiding prophylactic lymphectomy. An aggressive approach is indicated in case of local or distant recurrence to reduce hypercalcemia. Highlights: Management of parathyroid carcinoma is controversial due to its rarity and lack of large-scale series. Postoperative diagnosis is the most frequent scenario and requires a decision on possible surgical re-exploration. An aggressive approach is indicated in case of unclear surgical margins and local or distant recurrence.